If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 20 = 12x + -60 Reorder the terms: 20 + 2x = 12x + -60 Reorder the terms: 20 + 2x = -60 + 12x Solving 20 + 2x = -60 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 20 + 2x + -12x = -60 + 12x + -12x Combine like terms: 2x + -12x = -10x 20 + -10x = -60 + 12x + -12x Combine like terms: 12x + -12x = 0 20 + -10x = -60 + 0 20 + -10x = -60 Add '-20' to each side of the equation. 20 + -20 + -10x = -60 + -20 Combine like terms: 20 + -20 = 0 0 + -10x = -60 + -20 -10x = -60 + -20 Combine like terms: -60 + -20 = -80 -10x = -80 Divide each side by '-10'. x = 8 Simplifying x = 8
| 6x+62=10+14 | | 2t^3-9t^2-27=0 | | x^2+3x=117 | | 171-6x=30x+15 | | 34y+5=345 | | (8*20)2+(8*13)2-(5*3)3-(7*2)=x | | N*3=38 | | 101-6x=21x+23 | | 0=0.02d^2-2.6d+66.5 | | 4x^2-6x-12=0 | | -5+x+3=7 | | 10-2x-6=-x+5 | | (8*20)2+(8*13)2-(5*3)3-(7*2)= | | 50-2x=16x+16 | | 6x+6=106-10x | | 12x^2+19x=-5 | | (8*20)2+(8*13)2=X | | -7-9w=-7w-10 | | -5-6=-4x-(x+6) | | 9-x-2x=0 | | -5-6=-4-(x+6) | | (8*20)2=x | | N-15=22 | | x+3=40 | | 952=12d+28 | | 7x-4-3x=4x+8 | | -(7x-2)+5=3 | | 38-18=4(x-6) | | x-84=-0.5 | | h(t)=-2t^2+6t+3.5 | | x+5=-55 | | 5+x=5-x |